CLINICAL AND HEMATOLOGICAL PROFILE OF PATIENTS WITH DENGUE FEVER AT A TERTIARY CARE HOSPITAL: AN OBSERVATIONAL STUDY - BASAVARAJ GT; AVINASH ALASHETTY; CHANNAMMA G (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of this study was to analyze the clinical and hematological profile and studying outcome of patients having dengue fever (DF). Methods: This was an observational study conducted in the Department of General Medicine, Basveshwar Teaching and General Hospital, Kalaburagi, India. One hundred patients with DF were included in this study. Demographic details were obtained, detailed history was taken, and clinical examination was done. The cases were classified into dengue without warning signs, dengue with warning signs, and severe dengue as per world health organization classification of dengue. Clinical features, hematological profile, and outcome were assessed in studied cases. SSPE 21 software was used for statistical analysis. P value less than 0.05 was taken as statistically significant. Results: Out of these 100 cases, there were 62 (62.00 %) males and 38 (38 %) females with a M: F ratio of 1: 0.61. The mean age of male and female patients was found to be comparable with no statistically significant difference in the age group (p=0.391). Out of 100 studied cases, non-severe dengue was seen in 56 (56%) patients whereas 31 (31.00%) patients had non-severe dengue with warning signs and remaining 13 (13.00%) patients had severe dengue. The most common presenting complaint was fever which was present in all patients (100%). The other complaints included headache (82%) nausea and vomiting (74%). Positive torniquet test was seen in 7 (7%) patients and hypotension, decreased pulse pressure, and altered sensorium were seen in 5 (5%) patients each. In cases of dengue with warning signs or severe dengue out of 44 patients, 21 (21%) patients required blood component therapy and 5 (5%) patients landed up in shock despite fluid therapy. Two (2%) succumbed to complications of severe dengue. Conclusion: Comprehensive understanding of clinical features, hematological profile, and warning signs in DF is essential for timely diagnosis and effective management. With early diagnosis and proper management, the outcome of patients is usually good.